Root Architecture and Functional Traits of Spring Wheat Under Contrasting Water Regimes - Brunel-Saldias, Nidia; Ferrio, Juan Pedro; Elazab, Abdelhalim; Orellana, Massiel; del Pozo, Alejandro (Frontiers in Plant Science, 2020)
Wheat roots are known to play an important role in the yield performance under water-limited conditions. Three consecutive years trials (2015, 2016, and 2017) were conducted in a glasshouse in 160 cm length tubes on a set of spring wheat (Triticum aestivum L.) genotypes under contrasting water regimes (1) to assess genotypic variability in root weight density distribution in the soil profile, biomass partitioning and total water used; (2) to determine the oxygen and hydrogen isotopic signatures of plant and soil water in order to evaluate the contribution of shallow and deep soil water to plant water uptake and the evaporative enrichment of these isotopes in the leaf as a surrogate for plant transpiration. In the 2015 trial under well-watered conditions, the aerial biomass was not significantly different among 15 wheat genotypes, while the total root biomass and the root weight density distribution in the soil profile were significantly different. In 2016 and 2017 trials, a subset of five genotypes from the 2015 trial was grown under well-watered and water-limited regimes. The water deficit significantly reduced aerial biomass only in 2016. The water regimes did not significantly affect the root biomass and root biomass distribution in the soil depths for both the 2016 and 2017 trials. The study results highlighted that under a water-limited regime, the production of thinner roots with low biomass is more beneficial for increasing the water uptake than the production of large thick roots. The models applied to estimate the relative contribution of the plant's primary water sources (shallow or deep soil water) showed large inter-individual variability in soil, and plant water isotopic composition resulted in large uncertainties in the model estimates. On the other side, the combined information of root architecture and the leaf stable isotope signatures could explain plant water status.